Leprosy and American cutaneous leishmaniasis coinfection - Larissa Mondadori Mercadante; Marcel Alex Soares dos Santos; Elisangela Samartin Pegas; Bogdana Victória Kadunc (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Brazil is a country with a high prevalence of infectious diseases such as leprosy and leishmaniasis. However, coinfection of these diseases is still poorly understood. We report a case of a patient who presented with lepromatous leprosy and cutaneous-mucosal leishmaniasis at the same period. After clinical, laboratory, and histopathological diagnosis, the treatment was introduced and the patient showed important clinical improvement. He was followed in our outpatient clinic. Both pathologies play an important role in the immune system. Depending on the immune response profile of the host, diseases may present themselves in different ways. In this case, the patient showed a divergent immune response for each disease. We hypothesized that this response is specific for each pathogen.